QUALITY ANALYSIS OF SINGLE TREE OBJECT WITH OBIA AND VEGETATION INDEX FROM LAPAN SURVEILLANCE AIRCRAFT MULTISPECTRAL DATA IN URBAN AREA - Nurwita Mustika Sari; Dony Kushardono (Geoplanning: Journal of Geomatics and Planning, 2016)
High-resolution remote sensing data as the acquisition result of LAPAN Surveillance Aircraft (LSA) has the potential to analyze urban areas. The purpose of this study was to develop a method of LSA multispectral data utilization with an analysis of the single tree object in urban areas with OBIA and vegetation index. The method proposed in this study is a hierarchical classification to obtain the specific tree object that will be used further to analyze the quality of vegetation. In particular, analysis of the vegetation quality on the tree object was carried out by calculating the value of vegetation index NDVI. As a result, the overall accuracy of the hierarchical classification of objects in urban areas reached 88 %. In conclusion, the analysis of the quality of vegetation NDVI has been able to perceive the condition of trees in the urban area.